Karakteristik Fisikokimia Teh Kulit Manggis (Garcinia mangostana L.) Setelah Penambahan Kayu Manis (Cinnamomum cassia) dan Cengkeh (Syzygium aromaticum L.): Physicochemical Characteristics of Mangosteen Peel (Garcinia mangostana L.) Tea After Addition of Cinnamon (Cinnamomum cassia) and Clove (Syzygium aromaticum L.) - Pratiwi, Yunita Satya; Sanjaya, Yushinta Aristina; Rahmawati, Rahmawati; Rini, Dina Mustika (Departemen Gizi Masyarakat, Fakultas Ekologi Manusia, IPB dan PERGIZI PANGAN Indonesia, 2023)
Mangosteen (Garcinia mangostana L) contains xanthone compounds that are immunomodulatory, but cause a bitter taste in mangosteen peel tea. Therefore, it is necessary to add certain commodities such as cinnamon and cloves which are also rich in antioxidants. The objective of this study was to analyze the effect of cinnamon and clove addition on the physicochemical characteristics of mangosteen peel tea, and to compare the quality of mangosteen peel, cinnamon, and clove blended tea with SNI. The methods of this study was experimental research with a completely randomized design, statistical analysis using anova test and followed by post hoc tukey. The results of statistical test showed a significant effect at p<0.05. Physicoshemical result that will be compare with SNI Tea showed the total ash content of mangosteen peel tea was 2.86-4.04%, water-soluble ash content 37.05-24.16%, acid insoluble ash content 0.83-0.65%, ash alkalinity content 1.31-1.19, lead (Pb) content 1.53 mg/kg, and no detectable Hg metal content. Overall, there is an effect of cinnamon and clove addition on the physicochemical characteristics of mangosteen peel tea. Only formula M1KC1 (12 g mangosteen peel, 3 g cinnamon, and 3 g cloves) that fulfill the SNI Tea for total ash content, there are no samples that fulfill the SNI Tea standards for water-soluble ash content, all samples fulfill the SNI Tea for acid insoluble ash content, ash alkalinity, mercury (Hg), and lead (Pb).